2008
DOI: 10.1111/j.1537-2995.2008.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

The American Red Cross donor hemovigilance program: complications of blood donation reported in 2006

Abstract: The ARC data describe the current risks of blood donation in a model multicenter hemovigilance system using standardized definitions and reporting protocols. Reported reaction rates varied by regional center independently of donor demographics, limiting direct comparison of different regional blood centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
180
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(205 citation statements)
references
References 16 publications
17
180
3
5
Order By: Relevance
“…The high risk groups for VVRs are generally reported to be young, female, first-time donors [2,18,[25][26][27]. In our analysis, female gender was a significant risk factor in the univariate analysis in group I; however, it was not significant in the multivariate analysis in both group I and the overall group.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The high risk groups for VVRs are generally reported to be young, female, first-time donors [2,18,[25][26][27]. In our analysis, female gender was a significant risk factor in the univariate analysis in group I; however, it was not significant in the multivariate analysis in both group I and the overall group.…”
Section: Discussioncontrasting
confidence: 48%
“…The additional analysis that included more patients (the overall group) revealed that lower systolic blood pressure was the strongest independent predictor of VVR (OR = 2.45 (95% CI = 1.50-4.01), p < 0.001)). Our data add evidence that patients with a lower blood pressure are more susceptible to VVRs.The high risk groups for VVRs are generally reported to be young, female, first-time donors [2,18,[25][26][27]. In our analysis, female gender was a significant risk factor in the univariate analysis in group I; however, it was not significant in the multivariate analysis in both group I and the overall group.…”
contrasting
confidence: 48%
“…Hemovigilance during blood donation (BD) has been receiving increasing attention [1,2,3,4]. The European Guide to preparation, use and quality assurance of blood components listed adverse reactions related to BDs and included donor safety standards [5].…”
Section: Introductionmentioning
confidence: 99%
“…42 Hematom veya yatay biçimde kan sızıntısının kan bağışı merkezlerinde görülme sıklığı sırasıyla %0,32 ve %1,05'tir. 43,44 Bir çalışmada (n=19,076), lokal reaksiyonlar ile ilgili olarak, en sık görülen yan etkinin %0,07 oranında hematom olduğu tespit edilmiş-tir. 26 Diğer bir çalışmada (n=37896) tüm reaksiyonların %35'ini hematomların oluşturduğu bulunmuştur.…”
Section: Kan Bağişi Nedeni̇yle Geli̇şen Kompli̇kasyonlarunclassified